Pendampingan Administrasi Perizinan Usaha Dan Akuntansi Keuangan BUMDes Bebedahan Berkah - Asih Handayani; Anisa; Effriyanti (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2024)
This community service program aims to increase the capacity of managing business licensing administration and financial accounting at BUMDes Bebedahan Berkah. This assistance is carried out through a series of educational activities, technical training, and direct consultation with BUMDes administrators. The results of the activities show an increase in the understanding and ability of the management in managing business legality documents and preparing standardized financial reports. With proper implementation, it is expected that BUMDes can improve business governance in a more professional and sustainable